AMORPHOUS AND NANOCRYSTALLINE MATERIALS FOR APPLICATIONS AS HARD AND SOFT MAGNETS - Reiko Sato; Roland Grﬁssinger (Jurnal Sains Materi Indonesia, 2003)
In the last years great effort was made to improve the magnetic properties of hard and soft magnetic materials. Permanent magnets based on Nd-Fe-B with an energy product of45 1k J/m3 were recently reported Any significant further improvement needs a new compound with a higher saturation magnetization.